Paediatric workload of an adult retrieval service in Scotland. (February 2017) - Harry, Christina L.; Mccormack, Jon; Donald, Michael; Corfield, Alasdair R.
Abstract : The Emergency Medical Retrieval Service (EMRS) provides adults with life-threatening conditions in remote areas with timely interventions and rapid access to definitive medical care, including a primary response service. Paediatric patients are managed under a separate network. Despite this, there has been an increase in paediatric retrievals by EMRS. We aim to inform future service development and ascertain how EMRS can serve the needs of this cohort. This is a retrospective, observational study. Raw data were retrieved from the database of paediatric patients retrieved by EMRS for 9 years. A total of 112 paediatric patients were retrieved; 46% were primary retrievals. The most common injuries were head injuries ( n =29) and orthopaedic injuries ( n =16). Common interventions include fluid resuscitation ( n =34), ventilation ( n =22) and sedation/paralysis ( n =22).This study describes the evolution of an adult retrieval service to cover paediatric patients in Scotland outside the remit of the paediatric retrieval service.